Peran Minat Beli dalam Memediasi Rasa Percaya, Persepsian Harga dan Risiko terhadap Keputusan Pembelian - Salsabila, Hanif; Suliyanto, Suliyanto; Gunistiyo, Gunistiyo; Setyowati, Ratna Faridah (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the influence of consumer trust, price perception, and risk perception on purchasing decisions with purchase intention as a mediating variable at PT. Bangun Anugrah Beton Nusantara (PT. BABN). Respondents in this study were consumers who had purchased products from PT. BABN. A total of 145 respondents were selected using convenience sampling techniques. Data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) method with the help of Smart PLS 3.0 software. The results showed that consumer trust, price perception, and risk perception had a significant effect on purchase intention. However, only price perception and risk perception had a direct effect on purchasing decisions, while the direct effect of consumer trust was not significant. Purchase intention proved to be the strongest determinant in explaining purchasing decisions (32.5%) and effectively mediated the relationship between the three independent variables and purchasing decisions. This finding confirms that the company's marketing strategy should prioritize the formation of purchase intention to encourage consumer purchasing decisions.